Development of Student Worksheets based Assessment for Learning on Chemical Equilibrium to Improve Student Science Process Skills - Utami, Dianita Fitri; Agustini, Rudiana (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study focuses on creating Student Worksheets (LKPD) that incorporate Assessment for Learning principles to improve students' scientific process skills in chemical equilibrium. The research employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model of Research and Development (R&D). The study evaluates the LKPD's effectiveness, practicality, and validity. A one-sample t-test comparing pretest and posttest scores measures effectiveness. Practicality is determined through quantitative descriptive analysis of student feedback questionnaires and activity observation sheets. Validity assessment involves both qualitative and quantitative descriptive analysis using Likert scale validation forms. Results show that the developed LKPD achieved the highest possible validity score (mode of 5) across all aspects. It demonstrated 90.7% practicality and a statistically significant t-test result (p-value of 0.000). These outcomes suggest that the LKPD effectively enhances students' scientific process skills in chemical equilibrium studies. The Assessment for Learning approach and integrated feedback in the LKPD promote active student engagement and foster improved scientific process skills in this subject area.